2016
DOI: 10.1109/temc.2016.2515658
|View full text |Cite
|
Sign up to set email alerts
|

Measured Average Absorption Cross-Sections of Printed Circuit Boards from 2 to 20 GHz

Abstract: Absorption by the contents of an equipment enclosure, particularly printed circuit boards (PCBs), affect the enclosure's shielding performance. At high frequencies, this absorption can be quantified using the angle of arrival and polarization averaged absorption cross-section (ACS). However, there is no available data on the high-frequency absorption characteristics of modern PCBs. In this study, we apply a reverberation chamber to the determination of the average ACS of a large number of PCBs taken from conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…We see that the SE of an empty enclosure, , is as much a measure of its wall losses as it is of the transmission through its apertures [3], [4]. Furthermore, considering the cases where the enclosure is either empty or populated we find [3], [10] (2) which shows that knowledge of is in itself insufficient for predicting the SE of a populated enclosure. Indeed, the ATCS of an enclosure is a much more useful metric as it allows the SE of a populated enclosure to be predicted from the AACS of the contents using (2), under the assumption that in practical cases .…”
Section: A Rc Shielding Measurementmentioning
confidence: 94%
See 4 more Smart Citations
“…We see that the SE of an empty enclosure, , is as much a measure of its wall losses as it is of the transmission through its apertures [3], [4]. Furthermore, considering the cases where the enclosure is either empty or populated we find [3], [10] (2) which shows that knowledge of is in itself insufficient for predicting the SE of a populated enclosure. Indeed, the ATCS of an enclosure is a much more useful metric as it allows the SE of a populated enclosure to be predicted from the AACS of the contents using (2), under the assumption that in practical cases .…”
Section: A Rc Shielding Measurementmentioning
confidence: 94%
“…In [10] and [12] it is shown that the SE for a populated enclosure is (1) where is the total average transmission cross-section (ATCS) of the enclosure's apertures, is the total AACS of the inside of the enclosure walls and is the total AACS of the contents, including any antennas. This equation shows that both the total AACS of the contents and the total ATCS of the apertures directly determine the SE of the enclosure at high frequencies.…”
Section: A Rc Shielding Measurementmentioning
confidence: 99%
See 3 more Smart Citations